New Enantiomers of a Nor-Bisabolane Derivative and Two New Phthalides Produced by the Marine-Derived Fungus Penicillium chrysogenum LD-201810 - Ge, Yan; Tang, Wen-Li; Huang, Qing-Rong; Wei, Mao-Lian; Li, You-Zhi; Jiang, Lin-Lin; Li, Cheng-Lin; Yu, Xin; Zhu, Hong-Wei; Chen, Guo-Zhong; Zhang, Jian-Long; Zhang, Xing-Xiao (Frontiers in Microbiology, 2021)
Marine-derived fungi are a treasure house for the discovery of structurally novel secondary metabolites with potential pharmaceutical value. In this study, a pair of new nor-bisabolane derivative enantiomers (±)−1 and two new phthalides (4 and 5), as well as four known metabolites, were isolated from the culture filtrate of the marine algal-derived endophytic fungus Penicillium chrysogenum LD-201810. Their structures were established by detailed interpretation of spectroscopic data (1D/2D NMR and ESI-MS). The optical resolution of compound (±)−1 by chiral HPLC successfully afforded individual enantiomers (+)−1 and (−)−1, and their absolute configurations were determined by TDDFT-ECD calculations. Compound (±)−1 represents the first example of bisabolane analogs with a methylsulfinyl substituent group, which is rare in natural products. All of the isolated compounds 1–7 were evaluated for their cytotoxic activity against A549, BT-549, HeLa, HepG2, MCF-7, and THP-1 cell lines, as well as for antifungal activity against four plant pathogenetic fungi (Alternaria solani, Botrytis cinerea, Fusarium oxysporum, and Valsa mali). Compound 2, a bisabolane-type sesquiterpenoid, was shown to possess excellent activity for control of B. cinerea with half-maximal inhibitory concentration (IC50) of 13.6 μg/mL, whereas the remaining investigated compounds showed either weak or no cytotoxic/antifungal activity in this study.